Piloting the Transforming RN Roles in Community-Based Integrated Primary Care (TRIP): Student Responses. (3rd June 2021) - Beebe, Lora Humphrey; Mixer, Sandra J.; Taylor, Max; Hadjiharalambous, Chris Sissie; Craig, Jennifer; Turley, Debbie
Abstract: In this manuscript, we report the pilot results of the Transforming RN Roles in Community Based Integrated Primary Care (TRIP) undergraduate nursing curriculum. Junior nursing students participated in TRIP didactic, simulation and clinical activities and completed a focus group at the midpoint and conclusion of year one. Focus group themes addressed recruitment, understanding or primary care, connections between clinical and didactic, and team based care. TRIP offers the first comprehensive community based integrated primary care training for students in our region. Overall, the TRIP curriculum enhanced student learning and promoted leadership.